2019
DOI: 10.1152/ajpcell.00474.2018
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation facilitates the angiogenesis of human umbilical vein endothelial cells through MAPK/ERK signaling pathway by stimulating FGF2 secretion

Abstract: Electrical stimulation (ES) is able to enhance angiogenesis by stimulating fibroblasts. Fibroblast growth factor 2 (FGF2) is an independent angiogenesis inducer. The present study aimed to evaluate the role of ES-induced FGF2 secretion in affecting angiogenesis during wound healing via the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling pathway. Fibroblasts and human umbilical vein endothelial cells (HUVECs) were exposed to ES, and the HUVECs were cocultured with ES-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 39 publications
1
37
1
Order By: Relevance
“…In summary, the growth factors noted to be enhanced upon ES across the reviewed studies are FGF-1, FGF-2, and VEGF. These collectively aid in the proliferation of endothelial cells, fibroblasts, and expedites new vessel formation [ 51 ]. Table 4 summarizes key findings of in vivo and in vitro studies that investigate the effect of ES on this phase of healing [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the growth factors noted to be enhanced upon ES across the reviewed studies are FGF-1, FGF-2, and VEGF. These collectively aid in the proliferation of endothelial cells, fibroblasts, and expedites new vessel formation [ 51 ]. Table 4 summarizes key findings of in vivo and in vitro studies that investigate the effect of ES on this phase of healing [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, DC-induced activation of the PI3K/AKT pathway was also reported in different cell types, including neural progenitor cells [ 47 ], Schwann cells [ 48 ], and human umbilical vein endothelial cells (HUVEC) [ 49 ], as well as in ocular cells, including the corneal epithelium [ 6 , 50 ]. Activation of the MAPK signaling pathway is also reported through the application of EFs in neuronal cells [ 51 , 52 ], fibroblasts, HUVEC [ 53 ], and corneal epithelial cells [ 6 ]. Likewise, we also observed activation of PI3K/AKT and MAPK signaling pathways, along with other interconnected pathways, including T cell receptor signaling, Toll-like receptor signaling, TNF signaling, IL-17 signaling, FoxO signaling, and focal adhesion pathways, upon stimulation of corneal epithelial cells with oscillating EFs.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK/ERK signaling pathway is critical component in various processes including differentiation, proliferation, migration, and angiogenesis in a variety of human diseases development 31,32 . Clinical heterogeneity study on CLL showed that aberrant activation of MAPK‐ERK signaling promoted CLL cells proliferation and survival, and was closely related the dysregulation of homeostatic mechanisms in CLL cells 33 .…”
Section: Discussionmentioning
confidence: 99%